CHALLENGES OF TEACHING ARTS AT UNIVERSITY BETWEEN PEDAGOGY AND ANDRAGOGY PLASTIC ARTS AND CINEMA AS A MODEL - Riyadh Benchaib; Yahiya Bechlaghem (International Journal of Innovative Technologies in Social Science, 2025)
This study brings together the paradoxes of educational concepts focused on educating children and those focused on educating adults. It explores the question of variables and constants in the concept of andragogy. Furthermore, it seeks to define andragogy and related and adjacent concepts, taking into account the overlap between them, particularly in terms of their focus on teaching methods for adults, particularly in university settings, where students are not young learners to whom pedagogical concepts apply. This study also addresses the challenges of adult education in the fields of cinema and plastic arts, between university institutions whose primary concern is unconditional intellectual openness, and those whose sole concern is to build individuals and groups within political programs and specific agendas, whose sole concern is to integrate the individual within the collective mind of society or a single group, within the concept of the nation-state.